The law of innocence - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel., 2020)
"Defense attorney Mickey Haller utilizes his legal team's resources from behind bars to organize his own defense when he is framed for murder by an unknown adversary"--